FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA STRES KERJA PADA PEKERJA WANITA YANG MENJALANI WORK FROM HOME SELAMA MASA PANDEMI COVID-19 DI DKI JAKARTA - Dian Puspita; Choirunisha Nandya Iskandar (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Background and objective: The Jakarta has grown to become Indonesia's main job hub. Because of the rising prevalence of the COVID-19 virus epidemic, several businesses and government organizations have implemented work-from-home policies for their employees. Female employees who work from home, in particular, aren't just career women but also housewives who must balance these responsibilities so that jobrelated stress does not develop. Methods: This research aims to analyze the factors related to work stress toward female workers who worked from home during the Covid19 pandemic. This was a quantitative study using a cross-sectional design. Questionnaires were used to obtain the primary data. The research sample consists of female employees who work from home, with 97 respondents from the formal sector working in DKI Jakarta. Chi-square was used to evaluate the data. Result: The study showed that 97 respondents were over the age of 35, 39 respondents had an undergraduate education level, and the majority of respondents experienced a high mental workload and heavy work stress. The unrelated research variable were age (pvalue=0,103). The related research variables with work stress were marital status (pvalue=0,049) and mental workload (p-value=0,012). Conclusion : Female workers who work from home are expected to balance between adequate rest time and working at home during the COVID-19 pandemic so that work stress does not occur  Keywords: work frome home, women workers, work stress